Efficacy of acute care pathways for older patients: a systematic review and meta-analysis - Ijadi Maghsoodi A; Pavlov V; Rouse P; Walker CG; Parsons M (Springer Nature, 2022)
Meeting the needs of acute geriatric patients is often challenging, and although evidence shows that older patients need tailored care, it is still unclear which interventions are most appropriate. The objective of this study is to systematically evaluate the hospital-wide acute geriatric models compared with conventional pathways. The design of the study includes hospital-wide geriatric-specific models characterized by components including patient-centered care, frequent medical review, early rehabilitation, early discharge planning, prepared environment, and follow‐up after discharge. Primary and secondary outcomes were considered, including functional decline, activities of daily living (ADL), length-of-stay (LoS), discharge destination, mortality, costs, and readmission. A systematic review and meta-analysis were conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. A total of 20 studies reporting on 15 trials and acutely admitted patients with an average age of 79, complex conditions and comorbidities to acute geriatric-specific pathways (N = 13,595) were included. Geriatric-specific models were associated with lower costs (weighted mean difference, WMD = − $174.98, 95% CI = -$332.14 to − $17.82; P = 0.03), and shorter LoS (WMD = − 1.11, 95% CI = − 1.39 to − 0.83; P < 0.001). No differences were found in functional decline, ADL, mortality, case fatalities, discharge destination, or readmissions. Geriatric-specific models are valuable for improving patient and system-level outcomes. Although several interventions had positive results, further research is recommended to study hospital-wide geriatric-specific models.
Keywords: Acute geriatric pathways; Acute care for older persons; Meta-analysis; Systematic literature review; Randomized controlled trial